Analysis of Differentially Expressed Long Non-coding RNAs and the Associated TF-mRNA Network in Tongue Squamous Cell Carcinoma - Zhang, Mi; Chen, Zexi; Zhang, Sihui; Wu, Ling; Jie, Yinghui; Liao, Yunyang; Huang, Yue; Chen, Jiang; Shi, Bin (Frontiers in Oncology, 2020)
Accumulating evidence indicates that long noncoding RNAs (lncRNAs) play crucial roles in tongue squamous cell carcinoma (TSCC) tumorigenesis. However, the comprehensive regulation of lncRNAs‐transcription factors (TFs)‐messenger RNAs (mRNAs) in TSCC remains largely unknown. The purpose of this study was to identify aberrantly expressed lncRNAs and the associated TF‐mRNA network in TSCC. To explore lncRNA and mRNA expression profiles and their biological functions in TSCC, we surveyed the lncRNA and mRNA expression profiles of TSCC and adjacent tissues using next-generation RNA sequencing in six patients. Thousands of significantly differentially expressed lncRNAs (DELs) and mRNAs (DEGs) were identified. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed to demonstrate the principal functions of the significantly dysregulated lncRNAs and genes. A total of 40 DELs were screened between TSCC and adjacent noncancerous tissues. Results obtained from GEPIA and StarBase confirmed the expression levels of nine pivotal DELs obtained in our study. Three of the nine deregulated DELs were identified to have a significant impact on the overall survival of TSCC patients, which were evaluated with GEPIA and StarBase. LncMAP was used to predict the lncRNA‐TF‐mRNA triplets in TSCC. Furthermore, based on these results, we established lncRNA‐TF-mRNA coexpression networks for the up- and downregulated lncRNAs using Cytoscape. We also found that among the nine pivotal lncRNAs, there is limited research on the abnormally expressed lncRNAs, including RP11-54H7.4, CTD-2545M3.8, RP11-760H22.2, RP4-791M13.3 and LINC01405, in TSCC pathogenesis. Our findings provide a novel perspective and lay the foundation for future research on the potential roles of lncRNAs, TFs, and mRNAs in TSCC. Verification of the potential lncRNA‐TF‐mRNA regulatory networks will provide a more comprehensive understanding of the pathogenesis of TSCC.